IMPROVING STUDENT LEARNING OUTCOMES IN LEARNING THE PROBLEM OF STORIES IN MATHEMATICS USING SAINTIFIC APPROACH - Windi Rizkya Handayani; Lucky Miradi; Sukma Murni (IKIP Siliwangi, 2018)
This study aims to determine the learning of story problems with a scientific approach. Learning with a scientific approach is a learning process that is designed so that students actively construct concepts, laws or principles through stages of observing, formulating, proposing or formulating hypotheses on the mathematics learning outcomes of grade 2 students of SDN 091 Cibeureum. This research is a type of qualitative research, with experiments. The population is all grade 2 students with a total of 32 students. A learning process has an important role in the success of a learning. To create meaningful mathematical learning, student activity is needed in constructing the concepts and structure of the material. Based on learning observations in class 2, the learning carried out was mechanistic. That is, the teacher dominates learning while students only receive the material delivered by the teacher. Learning like this results in students not actively constructing knowledge in the learning process, thus impacting on the low learning outcomes of students themselves. The scientific approach is very suitable for the problems found because it has referred to constructivist learning theory. Therefore, this study was carried out to describe the application of a scientific approach to mathematics learning with a type of classroom action research (CAR). The research subjects were grade 2 students. This research was carried out in 2 cycles. The steps taken by the scientific approach are to observe, ask, collect information, reason, and communicate.